2017
DOI: 10.1186/s13098-017-0282-5
|View full text |Cite
|
Sign up to set email alerts
|

Aliskiren effect on non-alcoholic steatohepatitis in metabolic syndrome

Abstract: BackgroundNon-alcoholic steatohepatitis (NASH) is highly associated with metabolic syndrome, a major cause of morbidity in the globalized society. The renin–angiotensin system (RAS) influences hepatic fatty acid metabolism, inflammation and fibrosis. Thus, in the present study, we aimed to evaluate the effect of aliskiren, a direct renin inhibitor, on metabolic syndrome-related NASH.MethodsC57BL/6 male mice (n = 45) were divided into three groups: controls; animals inoculated with streptozotocin (STZ) (40 mg/k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 46 publications
(51 reference statements)
0
2
0
Order By: Relevance
“…The SIRT6 deficiency induced overactivation of IR and IGF1R in the heart tissue even without any change of blood insulin or glucose levels, which suggests that phosphorylation of IR and IGF1R is regulated by SIRT6 but not secondary effect of blood glucose or insulin (Sundaresan et al, ). It has been demonstrated that a high‐fat diet can decrease p‐IR levels and inhibit the activation of AKT, and also decrease glucose uptake and promote insulin resistance (Nguyen et al, ; Ramalho et al, ; Singh et al, ; Sodhi et al, ). Although insulin resistance is widely accepted as a risk factor of diabetes, it is a necessary response to evolutionary pressure when the main challenges to survival are not obesity and diabetes, but acute trauma and prolonged fasting (Soeters & Soeters, ).…”
Section: Discussionmentioning
confidence: 99%
“…The SIRT6 deficiency induced overactivation of IR and IGF1R in the heart tissue even without any change of blood insulin or glucose levels, which suggests that phosphorylation of IR and IGF1R is regulated by SIRT6 but not secondary effect of blood glucose or insulin (Sundaresan et al, ). It has been demonstrated that a high‐fat diet can decrease p‐IR levels and inhibit the activation of AKT, and also decrease glucose uptake and promote insulin resistance (Nguyen et al, ; Ramalho et al, ; Singh et al, ; Sodhi et al, ). Although insulin resistance is widely accepted as a risk factor of diabetes, it is a necessary response to evolutionary pressure when the main challenges to survival are not obesity and diabetes, but acute trauma and prolonged fasting (Soeters & Soeters, ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have pointed to the abnormal activity of TNF‐α as an important factor in the mechanism of liver injury (Muto et al, ; de la Mata et al, ; Sun, Tokushige, Isono, Yamauchi, & Obata, ). In this review, ALI was capable of reducing cytokine levels in cardiac, hepatic, and renal tissues (Bae et al, ; Karcioglu et al, ; Kishina et al, ; Lee et al, ; Lee et al, ; Ramalho et al, ; Takamura et al, ). Collagens are the main structural protein of the ECM (Pozzi, Wary, Giancotti, & Gardner, ; Yeh, Lin, & Tang, ).…”
Section: Discussionmentioning
confidence: 99%